Music Schools : In Search of Equity - Heimonen, Marja (Sibelius-Akatemia, 2024)
In this Symposium, my contribution explores the historical narratives of Finnish “out of school” music education, specifically, the basic arts education in music provided by music schools, from a legal-philosophical perspective. Despite Finland’s small population of approximately 5.6 million inhabitants (Statistics Finland 2024), the nation has produced a significant number of globally renowned musicians. This achievement is attributed to the country’s systematic “out of school” music education, which is supported by government funding. I will delve into the primary mechanisms employed by the state to support music education provided by music schools, tracing back to the late 1960s when the first Act (147/68) on state support for music schools was enacted, up to the present day.
Keywords: musiikkikasvatus; koulut; taiteen perusopetus; musiikkioppilaitokset; taidemusiikki; koulutus; oikeudenmukaisuus